HABITAT UTILIZED BY WILD TURKEY BROODS WITHIN OAK‐HICKORY FORESTS OF WEST VIRGINIA - James C. Pack; Ronald P. Burkert; William K. Igo; David J. Pybus (Wildlife Society Bulletin)
Abstract Oak‐hickory habitat utilized by 17 wild turkey (Meleagris gallopavo silvestris) broods was studied during a 5‐year period. Majority of brood activity occurred under a forest overstory. Characteristics of forest overstory including cover type, basal area, size‐density, average tree diameter, stand condition, site index, stand age along with aspect and slope were determined and tested for preferred use (P ≤ .10), family C.I. Habitat preference was tested for entire brood period, early brood period (May‐July 19) and late period (after July 19). Brood habitat appeared to be limited, and the area containing heavily used habitat was a minor portion of the home ranges. Broods preferred openings, white oak (Quercus alba) cover type, 9‐18 m2/ha (41‐80 ft2/acre) basal areas, medium stocked sawtimber stands, 0‐30% sloping terrain, and northern aspects. White pine (Pinus strobus), chestnut oak (Q. prinus), and Virginia pine (P. virginiana) cover types, clearcuts, basal areas equal to or exceeding 23 m2/ha (101 ft2/acre), slopes exceeding 30%, sapling stands, and east to southeast aspects were avoided.